THE INFLUENCE OF PASSIVE VOICE TOWARD STUDENTS’ WRITING ABILITY AT CLASS XI OF SENIOR HIGH SCHOOL DAARURRAHMAN WALANTAKA - Nina Fita Yuniarti; Welliam Hamer (TULIP (Tulisan Ilmiah Pendidikan), 2018)
The objective of the research was found out to determine whether there is the influence of writing before and after being given treatment with passive voice. Assume that there is a significant influence, as defined in the hypothesis that there is an effect of using passive voice toward writing. Especially writing on Narrative Text at Senior High School Daarurrahman. Passive voice is a media which is used to facilitate the students in understanding writing text. And passive voice more interesting and fun, so students don’t feel bored. The population of this research at class XI of senior high school in academic year 2017/2018 consist are 30 students . The technique of collecting data is test. More ever, this research was conducted through the following procedures: giving pretest, applying treatment, and giving post test. It was analyzed and processed by using calculation of paired t-test formula by using SPSS version 16.0. It proven by result of posttest was bigger than pre test with average score was 82,54 meanwhile pre test obtained 71,87. It means that the most improvement was in post test. Will based on the calculatiton of the paired sample t-test sig. P (value) was 0.00 and α = 0.05. It means that sig. P (value) <α = 0,05 and Ha is accepted. Base on the summary method of linier regression, it showed that value of correlation R 0,453. From the output obtained correlation determined (R Square) 0,210. It was indicated that the influence of X variable (passive voice) toward Y variable (writing Narrative Text) amount 21,0 %. It means that the treatments had influence of passive voice toward students' writing on narrative text.